Effect of BaO on optical, physical and radiation shielding properties of SiO2-B2O3-Al2O3-CaO- Na2O glasses system - S. Kaewjaeng (2018)
In this work, the effect of BaO on optical, physical and radiation shielding properties of SiO2-15B2O3-2Al2O3- 10CaO-23Na2O glasses have been investigated. Glasses in composition (50-x)SiO2:15B2O3:2Al2O3:10CaO:23Na2O: xBaO, where x = 0, 5, 10, 15 and 20 % mol were fabricated by melt-quenching technique. The results found that, the density and molar volume of glasses were increased with increasing of BaO concentration. The optical spectra were measured by uv-visible spectrophotometer and show shifted to longer wavelength. Gamma-ray shielding properties at 662 keV of SiO2-B2O-2Al2O3-10CaO-23Na2O-BaO glasses have been studied. The experimental results showed good agreement with the theoretical values, calculated by WinXCom. Moreover, the comparison of ordinary concrete and commercial window in term of half value layer has been investigated and show better radiation shielding properties with advantage of being transparent to visible light. From the theoretical calculation, the Compton scattering gives dominant contribution to the total mass attenuation coefficients for all studied glass samples. © 2010 Published by Elsevier Ltd.